Deformation coupled Moiré mapping of superlubricity in graphene - Bai, Huizhong (2023)
The ultralow friction of two-dimensional (2D) materials, commonly referred to as superlubricity, has been associated with Moiré superlattices (MSLs). While MSLs have been shown to play a crucial role in achieving superlubricity, the long-standing challenge of achieving superlubricity in engineering has been attributed to surface roughness, which tends to destroy MSLs. Here, we show via molecular dynamics simulations that MSLs alone are not capable of capturing the friction behavior of a multilayer-graphene-coated substrate where similar MSLs persist in spite of significant changes in friction as the graphene coating thickness increases. To resolve this problem, a deformation coupled contact pattern is constructed to describe the spatial distribution of the atomic contact distance. It is shown that as the graphene thickness increases, the interfacial contact distance is determined by a competition between increased interfacial MSLs interactions and reduced out-of-plane deformation of the surface. A frictional Fourier transform model is further proposed to distinguish between intrinsic and extrinsic contributions to friction, with results showing that thicker graphene coatings exhibit lower intrinsic friction and higher sliding stability. These results shed light on the origin of interfacial superlubricity in 2D materials and may guide related applications in engineering.